Beginning postcolonialism - McLeod, John (Beginnings (Manchester, England), 2000)
Designed for those studying postcolonialism for the first time, this is an introduction to the major areas of concern. It provides an overview of the emergence of postcolonialism as a discipline and examines many of its important critical writings. In particular, John McLeod demonstrates in practice how many of the ideas and concepts in the subject can be usefully applied when reading texts, as well as inviting students to develop their own views of postcolonialism.